Comment on: "Fault inversion vs. new thrust generation: A case study in the Malargüe fold-and-thrust belt, Andes of Argentina" by J. F. Mescua, and L. B. Giambiagi, Journal of Structural Geology 35 (2012) 51-63 - Dimieri, Luis Vicente (2012)
Comment